Perception of e-cigarette harm and benefit - a nationwide survey comparing characteristics between electronic cigarette users, conventional cigarette smokers and dual users - Caryn, Chan Mei Hsien; Ab Rahman, Jamalludin; Tee, Guat Hiong; Draman, Samsul; Nik Mohamed, Mohamad Haniki; Ho, Bee Kiau; Md Haris Robson, Noor Zurani; Kartiwi, Mira; Ab Rahman, Norny Syafinaz; Lim, Kuang Hock; Baharom, Nizam; Ismail, Norliana; et al. (Malaysia Medical Association, 2017)
Introduction: We conducted a nationally representative study to identify characteristics of current (e-cigarette users, conventional cigarette smokers, and dual users), former and never smokers linked to perceptions of harm and benefit associated with e-cigarette use. Methods: A crosssectional questionnaire survey of 1,987 adults (≥18 years) males was conducted via face-to-face interviews. Survey questions included sociodemographic and smoking-related variables, and questions relating to perceptions of harm and benefit associated with e-cigarette use. Logistic regression was used to identify sociodemographic characteristic linked to the perception of harm and benefit associated with e-cigarettes between types of EC users and smokers, with never smokers as the reference group. Results: Overall, older respondents aged ≥65 years (OR=1.736, CI 0.821-2.260), civil servants (OR=1.721, CI 1.085-2.729), non-governmental organisations (OR=1.570, CI 1.066-2.311) and the selfemployed (OR=1.469, CI 1.016-2.123) were more likely to perceive e-cigarettes as harmful. Conventional cigarette smokers (OR=0.759, CI 0.6090.946) as well as dual users (OR=0.537, CI 0.323-0.893) were less likely to perceive e-cigarettes as harmful. EC users (OR=8.353, CI 3.401-20.517), conventional cigarette smokers (OR=1.948, CI 1.497-2.537), dual users (OR=9.657, CI 5.300-17.596) and former smokers (OR=1.545, CI 1.1332.108), those younger (18-24 years, OR=2.252, CI 1.234-4.109; 25-44 years, OR=1.750, CI 1.055-2.903), were more likely to perceive e-cigarettes as beneficial. However, those with secondary education (OR=0.528, CI 0.379-0.736) and university or college degrees (OR=0.528, CI 0.379-0.736) were less likely to perceive e-cigarettes as beneficial. Discussion: Our findings constitute an important snapshot into the differences between types of EC users or smokers, as well as identifies characteristics associated with perceptions of EC harm and benefit in a nationally representative sample.